2007
DOI: 10.1103/physreve.76.031915
|View full text |Cite
|
Sign up to set email alerts
|

Local frequency density of states around field inhomogeneities in magnetic resonance imaging: Effects of diffusion

Abstract: A method describing NMR-signal formation in inhomogeneous tissue is presented which covers all diffusion regimes. For this purpose, the frequency distribution inside the voxel is described. Generalizing the results of the well-known static dephasing regime, we derive a formalism to describe the frequency distribution that is valid over the whole dynamic range. The expressions obtained are in agreement with the results obtained from Kubos line-shape theory. To examine the diffusion effects, we utilize a strong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 68 publications
0
21
0
1
Order By: Relevance
“…Though QSM profits from higher spatial resolution [41], Figure 4 suggests that tumor-related SBS can obviously be reliably detected based on 3 T GRE data that is routinely acquired in the course of SWI. Furthermore, the applied QSM technique neglects effects of diffusion due to variations in magnetic susceptibility which have been shown to influence the gradient-echo MRI signal [42], [43].…”
Section: Discussionmentioning
confidence: 99%
“…Though QSM profits from higher spatial resolution [41], Figure 4 suggests that tumor-related SBS can obviously be reliably detected based on 3 T GRE data that is routinely acquired in the course of SWI. Furthermore, the applied QSM technique neglects effects of diffusion due to variations in magnetic susceptibility which have been shown to influence the gradient-echo MRI signal [42], [43].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, from a different consideration, Ziener et al [15] showed that the density of states p(ω) of spherical particles with diffusion effect can be derived from the Laplace transformation of the MRI signal M 0 (t) without diffusion (see Eq. (13) in [15]):…”
Section: Diffusion Effect: Methodsmentioning
confidence: 99%
“…The implications of this model which is adapted from Krogh's capillary model [7] are described in detail in [8]. To understand the nature of the relaxation processes involved in contrast generation by nanoparticles, we analyze the CPMG relaxation rate, free induction decay and the time evolution of a spin echo in dependence on the relevant parameters.…”
Section: Introductionmentioning
confidence: 99%